Conceptual Model Measurement of Total People’s Defense and Security System Readiness Based on Land Defense - Fulkan Kafilah Al Husein; Alfema Kansha Nandita; Chrisdiego Chrisanto; Ro'fah Nur Rachmawati (Jurnal Pertahanan: Media Informasi ttg Kajian & Strategi Pertahanan yang Mengedepankan Identity, Nasionalism & Integrity, 2023)
The Universal People's Defence and Security System (Sishankamrata) is a critical component of Indonesia's national defence strategy. This study proposes the Index of Basic Military Capacity (IKMR) as a reliable and valid measuring instrument to ensure the readiness of its civilian population in facing protracted warfare. we used the Partial Least Squares-Structural Equation Modelling (PLS-SEM) method to test the relationships between selected variables, validate constructs, and measure the reliability of each variable in developing the IKMR. Our innovative approach enables the government to determine a more effective strategy based on measurement results, ensuring that the civilian population is adequately prepared to defend the sovereignty, territorial integrity, and national safety of the country. This study makes a significant contribution to defence research by proposing conceptual model index as the basic of assessing sishankamrata in an exact population.